Bioequivalence Studies for Two Different Strengths of Montelukast in Healthy Volunteers: 10 mg Film-coated Tablets and 5 mg Chewable Tablets - Pedroso, P.; Almeida, S.; Filipe, A.; Neves, R. I.; Boudreault, S.; Jiménez, C. (Drug Research, 2013)
In order to assess the bioequivalence of 2 different formulations of montelukast, a pivotal trial for the montelukast 10 mg film-coated tablets formulation and a pivotal trial for the montelukast 5 mg chewable tablets formulation were conducted.For the 10 mg study, 34 healthy subjects were enrolled in a single centre, randomised, single-dose, open-label, 2-way crossover study, with a minimum washout period of 7 days, while for the 5 mg study, 42 healthy subjects were included in another study with a similar design. For both studies, plasma samples were collected up to 24 h post-dosing and drug levels were determined by reverse liquid chromatography and detected by tandem mass spectrometry detection.Pharmacokinetic parameters used for bioequivalence assessment, area under the concentration-time curve from time zero to time of last non-zero concentration (AUC0–t) and from time zero to infinity (AUC0–inf) and maximum observed concentration (Cmax), were determined from the drug concentration data using non-compartmental analysis.In the 10 mg study, the 90% confidence intervals obtained by analysis of variance were 99.62–120.51% for Cmax, 102.25–117.37% for AUC0–t and 101.96–116.67% for AUC0–inf, which were within the predefined acceptable range of 80.00–125.00%.In the 5 mg study, the 90% confidence intervals were 91.14–98.46% for Cmax, 93.02–98.42% for AUC0–t and 93.09–98.63% for AUC0–inf, which were within the predefined acceptable range of 80.00–125.00%.Bioequivalence between formulations was concluded both in terms of rate and extent of absorption for both strengths.
Keywords: montelukast; Bioequivalence; AUC; Cmax; CAS number 158966-92-8